Emerging Immersive Communication Systems: Overview, Taxonomy, and Good Practices for QoE Assessment - Pérez, Pablo; Gonzalez-Sosa, Ester; Gutiérrez, Jesús; García, Narciso (Frontiers in Signal Processing, 2022)
Several technological and scientific advances have been achieved recently in the fields of immersive systems (e.g., 360-degree/multiview video systems, augmented/mixed/virtual reality systems, immersive audio-haptic systems, etc.), which are offering new possibilities to applications and services in different communication domains, such as entertainment, virtual conferencing, working meetings, social relations, healthcare, and industry. Users of these immersive technologies can explore and experience the stimuli in a more interactive and personalized way than previous technologies (e.g., 2D video). Thus, considering the new technological challenges related to these systems and the new perceptual dimensions and interaction behaviors involved, a deep understanding of the users’ Quality of Experience (QoE) is required to satisfy their demands and expectations. In this sense, it is essential to foster the research on evaluating the QoE of immersive communication systems, since this will provide useful outcomes to optimize them and to identify the factors that can deteriorate the user experience. With this aim, subjective tests are usually performed following standard methodologies (e.g., ITU recommendations), which are designed for specific technologies and services. Although numerous user studies have been already published, there are no recommendations or standards that define common testing methodologies to be applied to evaluate immersive communication systems, such as those developed for images and video. Taking this into account, a revision of the QoE evaluation methods designed for previous technologies is required to develop robust and reliable methodologies for immersive communication systems. Thus, the objective of this paper is to provide an overview of existing immersive communication systems and related user studies, which can help on the definition of basic guidelines and testing methodologies to be used when performing user tests of immersive communication systems, such as 360-degree video-based telepresence, avatar-based social VR, cooperative AR, etc.